2015
DOI: 10.3892/mmr.2015.3812
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α and Wnt/β-catenin signaling pathways promote the invasion of hypoxic gastric cancer cells

Abstract: The present study aimed to examine the association between hypoxia-inducible factor (HIF)-1α and the Wnt/β-catenin signaling pathway in a hypoxic environment. The study also aimed to explore the possible mechanisms underlying the invasion of hypoxic gastric cancer cells in vitro and in vivo. The pcDNA™ 6.2-GW/EmGFP-miR-β-catenin plasmid was transfected into SGC-7901 gastric cancer cells, resulting in cells with stable suppression of β-catenin expression. The biological characteristics of the control, liposome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 25 publications
4
31
1
Order By: Relevance
“…Surprisingly, hypoxia (24 hours) did not affect invasiveness although previous studies have shown hypoxia to promote the invasiveness of human PCa cells [eg 45,46 ]. Indeed, the effect of hypoxia in promoting cellular invasiveness has been reported also for other cancers, for example colon, 34 breast 47,48 and gastric cancer 49 . The apparent lack of effect in the present study could be due to the “normoxic” Mat‐LyLu cells also having some properties usually associated with hypoxia.…”
Section: Discussioncontrasting
confidence: 71%
“…Surprisingly, hypoxia (24 hours) did not affect invasiveness although previous studies have shown hypoxia to promote the invasiveness of human PCa cells [eg 45,46 ]. Indeed, the effect of hypoxia in promoting cellular invasiveness has been reported also for other cancers, for example colon, 34 breast 47,48 and gastric cancer 49 . The apparent lack of effect in the present study could be due to the “normoxic” Mat‐LyLu cells also having some properties usually associated with hypoxia.…”
Section: Discussioncontrasting
confidence: 71%
“…We asked the question whether the extremely low levels of uPA/ uPAR as determined in rd10 mice might depend on retinal expression of HIF-1. In models of ocular pathologies characterized by HIF-1 up-regulation, uPAR is overexpressed in response to ischaemic conditions 15 suggesting a causal relationship with HIF-1 accumulation also in line with the finding that in tumour angiogenesis, HIF-1 mediates the transcription of uPA/uPAR genes during hypoxia 36,37 In this respect, mouse models of retinal degeneration as the This study also provides evidence that systemic administration of UPARANT may be an effective, non-invasive approach to alleviate the pathological signs of RP.…”
Section: Hif-1 Regulation Of Upa/upar Expressionsupporting
confidence: 54%
“…Certain studies have suggested that HIF-1α activation regulates the Wnt/β-catenin signaling pathway, which activates the expression of target genes and contributes to the enhanced invasion of hypoxic gastric cancer cells (35)(36)(37). CD44 is a target gene of the Wnt/β-catenin signaling pathway (38); therefore, the mechanism by which HIF-1α regulates CD44 may be associated with the Wnt/β-catenin signaling pathway in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%